Cellular differentiation of non-transformed intestinal epithelial cells is regulated by Lactobacillus rhamnosus and L. casei strains - Kolinska, J; Zakostelecka, M; Zemanova, Z; Lisa, V; Golias, J; Kozakova, H; Dvorak, B (Physiological research, 2018)
The aim of this study was to characterize an in vitro modulating effect of three commensal Lactobacillus strains on cellular differentiation of non-transformed crypt-like rat small intestinal cell line IEC-18. IEC-18 was grown on extracellular matrix, with or without presence of Lactobacillus strains. Gene expression of IEC-18 bacterial detection system - such as Toll-like receptors TLR-2, TLR-4, signal adapter MyD88, cytoplasmic NOD2 receptor, inflammatory cytokines IL-18, IL-1beta, chemokine IL-8 and enzyme caspase-1 - was evaluated using real-time PCR. Expression and localization of TLR-2, TLR-4, IL-18 and caspase-1 proteins was demonstrated by Western blotting and immunofluorescent staining. Secretion of IL-18 to apical and basolateral surfaces was assayed by ELISA. Our results suggested that L. casei LOCK0919 accelerated differentiation of IEC-18 by stimulating TLR-2, TLR-4, MyD88, IL-18, caspase-1 mRNAs and proteins. L. casei LOCK0919 increased expression and transfer of villin and beta-catenin from cytoplasm to cell membrane. Presence of L. rhamnosus LOCK0900 resulted in detachment of IEC-18 layer from extracellular matrix leading to induction of IL-1beta, of TLR-2 and IL-8 mRNAs and stimulation of MyD88, caspase-1 and cytosolic receptor NOD2 mRNAs. L. rhamnosus LOCK0908 was not recognized by TLR-2 or TLR-4 receptors. Lactobacilli-IEC-18 crosstalk enhanced immune and barrier mucosal functions.
Keywords: Subcellular Fractions; interleukin-18; Animals; Intestinal Mucosa; beta-katenin; Probiotics; Lactobacillus casei; Cytokines; subcelulární frakce; mikrofilamentové proteiny; cytokiny; buněčná diferenciace; Epithelial Cells; Lacticaseibacillus casei; messenger RNA; kaspasa 1; RNA, Messenger; regulace genové exprese; probiotika; Caspase 1; krysa rodu Rattus; Toll-Like Receptors; Cell Differentiation; Gene Expression Regulation; zvířata; Interleukin-18; toll-like receptory; Lacticaseibacillus rhamnosus; Microfilament Proteins; beta Catenin; epitelové buňky; Rats; střevní sliznice